Lipid composition of the hydrothermal vent clam Calyptogena pacifica (Mollusca: Bivalvia) as a trophic indicator - Allen, C E; Tyler, P A; Van Dover, C L (Journal of the Marine Biological Association of the United Kingdom, 2001)
Specimens of the chemoautotrophic symbiont-bearing hydrothermal vent clam Calyptogena pacifica were collected from hydrothermal vents at the Endeavour segment of the Juan de Fuca Ridge. Total lipid was extracted from gill, foot and mantle tissues, and lipid class and fatty acid composition determined by thin layer chromatography with flame ionization detection (TLC–FID), gas chromatography (GC) and gas chromatography with mass spectrometry (GC–MS). An abundance of n–7 monounsaturated fatty acids (MUFA), especially in the gill, reflected the large contribution of chemoautotrophic symbiotic bacteria to the nutrition of this clam. The absence of n–8 MUFA suggests that C. pacifica does not contain methanotrophic symbiotic bacteria. Low levels of highly unsaturated fatty acids (HUFA) such as 20:5 n–3 and 22:6 n–3 were detected in C. pacifica and their presence is attributed to a source other than chemoautotrophic symbiotic bacteria. Significant levels of non-methylene interrupted dienoic fatty acids and eicosatrienoic acid (20:3) were also detected in C. pacifica and it is suggested that these fatty acids are synthesized from n–7 MUFA as alternatives to HUFA. In contrast to shallow water bivalves, elevated levels of triglyceride were detected in the gills compared to the mantle.